Knowledge and Preventive Practice of Urinary Tract Infection among Bangladeshi Female Ready-made Garments Worker (East West Medical College Journal, 2024)
Ready-made garments (RMG) are Bangladesh’s largest export earner sector, with 800,000 workers, including two-thirds of females. Female RMG workers suffer from various illnesses, including urinary tract infections (UTI), but data is scars related it in Bangladesh. Therefore, the study aimed to evaluate the knowledge and preventive practice of UTI among female RMG workers. Method: This cross-section survey was conducted to evaluate the knowledge and preventive practice of UTI among female RMG workers. Using convenient sampling technique, we collected 351 data between February to April 2021 from two RMG. Data were analysed by using Statistical Package Social Science (SPSS) software version 23. Descriptive statistics was conducted using frequencies and proportions. Chi-square test was used to determine the association between dependent and independent variables. Linear regression and Pearson co-relation was used to determine the association between knowledge and practice. Results: Of 351 participants, 22% had good knowledge and 33% were in good practice. The study found a statistically significant correlation between knowledge level of UTI and participants’ age, education, residence, family size, parents’ education and occupation (p